India and the knowledge economy : leveraging strengths and opportunities - Dahlman, Carl J., 1950- (WBI development studies., 2005)
"India can do much more to leverage its strengths and seize today's opportunities. India and the Knowledge Economy suggests actions to strengthen its economic and institutional regime, develop educated and skilled workers, create an efficient innovation system, and build a dynamic information infrastructure. In so doing, it will be able to improve its international competitiveness and join the ranks of countries that are making a successful transition to the knowledge economy."--Jacket